2011
DOI: 10.1007/s13187-011-0244-9
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Rural Women in Nicaragua the Principles of Breast Health

Abstract: Breast cancer has emerged as an important health condition worldwide, including developing countries. Screening is limited or non-existent in resource-poor areas. The purpose of this study was to assess knowledge, attitudes, and practices of self (SBE) and clinical (CBE) breast examinations among 198 rural Nicaraguan women. Ten (5.1%) had performed a SBE, and 16 (8.1%) had a CBE. CBE was significantly associated with a pre-instruction total score of 70% or greater (OR = 13.7, 95% CI = 1.26, 149.70, p = 0.03). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“… 16 However, according to one article from Brazil, this knowledge was not always associated with BSE knowledge or practice. 27 Although research in Nicaragua pointed to a positive association between FH and BSE, more than half of women studied believed they did not have a personal BCA risk, 12 although the converse was found in a study from Chile, where participants overestimated their risks. 7 …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“… 16 However, according to one article from Brazil, this knowledge was not always associated with BSE knowledge or practice. 27 Although research in Nicaragua pointed to a positive association between FH and BSE, more than half of women studied believed they did not have a personal BCA risk, 12 although the converse was found in a study from Chile, where participants overestimated their risks. 7 …”
Section: Resultsmentioning
confidence: 94%
“…The reviewed articles revealed the range of women’s knowledge about BCA and prevention, including the finding that knowledge seems to be related to the degree to which screening and diagnosis are delayed. 20 A study found that Nicaraguan women who were more knowledgeable about breast health were significantly more likely to have a CBE 12 ; in Mexico, most women in one study reported having received vague information about BCA and were most knowledgeable about physical changes associated with its presentation. 26 Women in Brazil, when questioned about specific screening tests, revealed that approximately 77% were aware of at least one screening modality, but nearly 40% were not able to correctly name the examination, and approximately 20% were not aware of any examination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 The study concluded that the intention to seek preventive health behaviors was found to have a strong influence on BSE. Another study utilized a community-based health project to increase breast health awareness in rural Nicaraguan women 20 and found that women who participated in the program were receptive to learning about breast health and agreed to perform a BSE monthly; the community-based program was also effective for BSE training and breast health promotion in the LMIC setting. In another community-based interventional study in Pakistan, health education on BSE and testicular self-examination was successful, 21 with post-intervention assessments showing a significant improvement (of 83% and 72%, respectively; P G .001) in self-examination knowledge among study participants.…”
mentioning
confidence: 99%